2015
DOI: 10.1098/rspa.2015.0380
|View full text |Cite
|
Sign up to set email alerts
|

Bounding the plastic strength of polycrystalline voided solids by linear-comparison homogenization techniques

Abstract: The elastoplastic response of polycrystalline voided solids is idealized here as rigid-perfectly plastic. Bounds on the macroscopic plastic strength for prescribed microstructural statistics and single-crystal strength are computed be means of a linearcomparison homogenization technique developed by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The outcomes of these first studies are valuable but show some limitation. First, numerical homogenization have shown that macroscopic yield surfaces of macroscopically isotropic polycristalline aggregates with intergranular voids are quite distinct from the ones obtained by supposing that voids are in a von Mises isotropic matrix (Lebensohn et al, 2011;Nervi and Idiart, 2015). Then, at the mesoscale of the porous boundaries, all isotropic models previously mentioned are intrinsically not adapted to model complex effects coupling crystallographic orientations, material non-linearity and void size/shape.…”
Section: Crystal Latticementioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of these first studies are valuable but show some limitation. First, numerical homogenization have shown that macroscopic yield surfaces of macroscopically isotropic polycristalline aggregates with intergranular voids are quite distinct from the ones obtained by supposing that voids are in a von Mises isotropic matrix (Lebensohn et al, 2011;Nervi and Idiart, 2015). Then, at the mesoscale of the porous boundaries, all isotropic models previously mentioned are intrinsically not adapted to model complex effects coupling crystallographic orientations, material non-linearity and void size/shape.…”
Section: Crystal Latticementioning
confidence: 99%
“…In order to obtain a criterion for porous grain boundaries with ellipsoidal voids, a variational approach is adopted in the following. Indeed, variational methods provide a homogenization alternative to limit analysis that has proven fruitful for the study of voided viscoplastic single crystals (Han et al, 2013;Mbiakop et al, 2015a;Song and Ponte-Castañeda, 2017a) and polycrystals (Lebensohn et al, 2011;Nervi and Idiart, 2015;Song and Ponte Castañeda, 2018). In particular, they are expected to yield viscoplastic potentials and to be more convenient to introduce void shape effects.…”
Section: Viscoplastic Potentials For Porous Bi-crystals With Ellipsoi...mentioning
confidence: 99%